The hidden curriculum in Singapore's secondary schools - Phua, Kelyn (2016)
The research uses in-depth interviews to find out what really goes on beneath the internationally acclaimed educational system. It reveals the extent to which experiences in top schools and less branded schools differ in terms of the socialization experience, perceptions, expectations and the social implications that could possibly have on the society. It interviews Express stream students and finds differentiated experiences between and within schools in terms of culture and curriculum. It shows the effects of social influence with regards to academic achievements and evaluates educational choices through constructed meanings. It argues that the educational structure perpetuates intellectual segregation and thus, inequality.